Management of hepatocellular carcinoma with portal vein tumor thrombosis: Review and update at 2016 - Chan, Stephen L (World J Gastroenterol, 2016)
Portal vein tumor thrombosis (PVTT) is a common phenomenon in hepatocellular carcinoma (HCC). Compared to HCC without PVTT, HCC with PVTT is characterized by an aggressive disease course, worse hepatic function, a higher chance of complications related to portal hypertension and poorer tolerance to treatment. Conventionally, HCC with PVTT is grouped together with metastatic HCC during the planning of its management, and most patients are offered palliative treatment with sorafenib or other systemic agents. As a result, most data on the management of HCC with PVTT comes from subgroup analyses or retrospective series. In the past few years, there have been several updates on management of HCC with PVTT. First, it is evident that HCC with PVTT consists of heterogeneous subgroups with different prognoses. Different classifications have been proposed to stage the degree of portal vein invasion/thrombosis, suggesting that different treatment modalities may be individualized to patients with different risks. Second, more studies indicate that more aggressive treatment, including surgical resection or locoregional treatment, may benefit select HCC patients with PVTT. In this review, we aim to discuss the recent conceptual changes and summarize the data on the management of HCC with PVTT.